Assessment of Chemical Treatment on Hemp Fiber Utilized as Reinforcement in Polymer Composites: Association of Thermal Degradation and Activation Energy of Fiber - Priyanka Soni; Shishir Sinha (Journal of Natural Fibers, 2022)
The primary purpose of the research is to improve the surface of hemp fibers chemically. The outcome of different chemical treatments of fibers on their chemical, morphological, physical, and thermal properties has been studied. The fiber was treated with 5w/v % alkali solution for different time intervals and with 5 w/v % silane solution. The fiber properties were analyzed using FTIR (Fourier transform spectroscopy), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy-dispersive X-ray analysis (EDX). Two different methods, i.e., Flynn-Wall-Ozawa (F-W-O) and Kissinger-Akahira-Sunose (K-A-S) methods, were utilized to calculate the degradation activation energy and analyze thermal kinetics of untreated and treated fibers. The alkali treated fibers for 30 min show the maximum increment in average activation energy from 141 kJmol−1 to 175 kJmol−1. At 30 min, the alkali treatment of fibers shows the best thermal properties, and afterward, the fiber starts to degrade. The results obtained from silane treatment are satisfactory but not on par with results obtained from alkali treatment.